The Association of Plant-Based Diet With Cardiovascular Disease and Mortality: A Meta-Analysis and Systematic Review of Prospect Cohort Studies - Quek, Jingxuan; Lim, Grace; Lim, Wen Hui; Ng, Cheng Han; So, Wei Zheng; Toh, Jonathan; Pan, Xin Hui; Chin, Yip Han; Muthiah, Mark D.; Chan, Siew Pang; Foo, Roger S. Y.; Yip, James; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The association between plant-based diets and cardiovascular disease (CVD) remains poorly characterized. Given that diet represents an important, modifiable risk factor, this study aimed to assess (1) the relationships between impact of adherence to plant-based diets on cardiovascular mortality, incident CVD, and stroke; (2) if associations differed by adherence to healthful and less healthful plant‐based diets. Methods and Findings: Medline and Embase databases were searched up to May 2021. Studies assessing CVD outcomes with relation to plant-based dietary patterns or according to plant-based dietary indices (PDI) were included. A meta-analysis of hazard ratios (HR) was conducted using DerSimonian and Laird random effects model. Thirteen studies involving 410,085 participants were included. Greater adherence to an overall plant-based dietary pattern was significantly associated with lower risk of cardiovascular mortality (pooled HR: 0.92, 95% CI: 0.86-0.99 p=0.0193, I2= 88.5%, N= 124,501), and lower risk of CVD incidence (pooled HR: 0.90, 95% CI: 0.82-0.98, p=0.0173, I2=87.2%, N=323,854). Among the studies that used PDI, unhealthful plant-based diets were associated with increased risk of cardiovascular mortality (pooled HR: 1.05, 95% CI: 1.01-1.09, p= 0.0123, I2= 0.00%, N= 18,966), but not CVD incidence. Conversely, healthful plant-based diets were associated with decreased CVD incidence (pooled HR: 0.87, 95% CI: 0.80-0.95, p= 0.0011, I2=57.5%, N= 71,301), but not mortality. Vegetarians also had significantly lower CVD incidence (HR: 0.81, 95% CI: 0.72-0.91, p=0.0004, I2=22.2%, N=16, 254) but similar CVD mortality or stroke risk when compared to the meat-eaters. Conclusion: To date, this comprehensive study examines the effects of plant-based diet on major clinical endpoints using more holistic PDIs. These findings highlight the favorable role of healthful plant-based foods in reducing cardiovascular mortality and CVD.